Incentives for Retrieval Practice and Exam Performance of College Students - Fady Mansour; Stefani Milovanska-Farrington; Nour Kattih; Mohammed Saeed (Institute of Labor Economics (IZA), 2025)
Literature shows that retrieval of knowledge improves students' performance on exams (e.g., McDaniel et al. 2007; Roediger et al. 2011). In this study, we provide students in online and face-to-face Principles of Macroeconomics courses with practice questions that resemble the ones given on an actual exam and require a sample of the students to submit their answers. Then, we examine whether making the submission of the practice questions mandatory improves students' performance on actual exams. We find evidence that required submission of the questions for preparation for the first exam during the semester is associated with a higher score on these questions. The score students earn on the practice questions offered about a week before each exam (first, second and a final) is also positively related to the respective actual test grade. Additionally, better performance on each exam predicts a higher grade on the following exam(s), especially for online courses. The results indicate the importance of providing incentives for students to prepare for exams through retrieval practice.
Keywords: A20; A22; I21; 330; test preparation; principles of macroeconomics; exam performance; undergraduate teaching